2021
DOI: 10.3390/ijms22115803
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Extracellular Vesicle miRNAs Can Identify Lung Cancer, Current Smoking Status, and Stable COPD

Abstract: Lung cancer remains the leading cause of cancer related mortality worldwide. We aimed to test whether a simple blood biomarker (extracellular vesicle miRNAs) can discriminate between cases with and without lung cancer. Methods: plasma extracellular vesicles (EVs) were isolated from four cohorts (n = 20 in each): healthy non-smokers, healthy smokers, lung cancer, and stable COPD participants. EV miRNA expression was evaluated using the miRCURY LNA miRNA Serum/Plasma assay for 179 specific targets. Significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…are significantly enriched in EVs in blood during lung infection and injury [ 125 ], and these miRNAs play important regulatory roles. Coincidentally, O’Farrell, H.E et al demonstrated [ 126 ] that miRNAs in EVs from plasma have key biological information specific to lung cancer. Fifteen miRNAs, including miR-199a-5p, were differentially expressed between lung cancer patients and healthy non-smoking participants.…”
Section: Resultsmentioning
confidence: 99%
“…are significantly enriched in EVs in blood during lung infection and injury [ 125 ], and these miRNAs play important regulatory roles. Coincidentally, O’Farrell, H.E et al demonstrated [ 126 ] that miRNAs in EVs from plasma have key biological information specific to lung cancer. Fifteen miRNAs, including miR-199a-5p, were differentially expressed between lung cancer patients and healthy non-smoking participants.…”
Section: Resultsmentioning
confidence: 99%
“…A further study made it possible to identify EVs-miRNAs as diagnostic biomarkers to distinguish patients with lung cancer and patients with COPD, as well as to determine the differences between smokers suffering from these pathologies [ 83 ]. In this study, O’Farrell et al have demonstrated the applicability of EVs-miRNAs as a screening tool for patients with COPD or lung cancer.…”
Section: Evs-mirna As Therapeutic Tools In Chronic Respiratory Diseasesmentioning
confidence: 99%
“…Furthermore, it has also been reported that airway inflammation and airway remodeling are exacerbated by activation of JNK1/2-MMP-9 pathway associated with ORMDL3 knockdown in asthmatic mice, suggesting that miR-192-5p mediates airway remodeling and autophagy by other signaling pathways (65). Abnormal expression has been reported for miR-451a in pulmonary diseases associated with remodeling processes, as elevated levels of expression have been demonstrated in patients with chronic obstructive pulmonary disease (COPD) (66). Several miRs, such as miR-19a, miR-142, and miR-221, have been found to be differentially expressed in asthma and associated with airway remodeling (67)(68)(69).…”
Section: Non-coding Rnas In Airway Remodeling Processesmentioning
confidence: 99%